PENGARUH KEPUASAN KERJA TERHADAP KETERIKATAN KARYAWAN DIMEDIASI OLEH KERJA TIM - Afifah, Ayu Yuni (Fakultas Ekonomi Universitas Wisnuwardhana, 2020)
Abstract: The phenomenon of millennials massive entry into the working environment in the last decade brought different characteristics with the previous generations. The negative stigma attached to the millennials reinforced the cirmcumstances that millennials’ engagement level at work was low although their job satisfaction was high. This research aimed to examine the implication of teamwork in mediating job satisfaction and employee engagement. This study involved 129 respondents and used SmartPLS 3.2.8 as an analysis tool. This study suggests that job satisfaction significantly affecting employee engagement but partially mediated by teamwork. This research provides insights for companies, how to maintain millennials at work. Keywords: employee engagement, job satisfaction, teamwork, millennials